On D- Compact Topological Groups - AL– Khafajy, Dheia; Sadek, Afraa (Iraqi Journal of Science, 2024)
In the present paper, we have introduced some new definitions On D- compact topological group and D-L. compact topological group for the compactification in topological spaces and groups, we obtain some results related to D- compact topological group and D-L. compact topological group.